2020
DOI: 10.3892/mmr.2020.11529
|View full text |Cite
|
Sign up to set email alerts
|

YAP‑mediated crosstalk between the Wnt and Hippo signaling pathways (Review

Abstract: Yes-associated protein (YaP) acts as a transcriptional co-activator in gene expression and cell proliferation control by binding to the transcriptional factor Tea domain (Tead) of the Hippo signaling pathway in the nucleus, and also acts as a regulator by binding to another transcriptional co-activator, β-catenin of the Wnt signaling pathway. Whether YaP preferentially acts as a transcriptional co-regulator of the activity of the Hippo signaling pathway or as a regulator in the Wnt signaling pathway depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 56 publications
4
41
0
Order By: Relevance
“…A recent review on YAP describes its crosstalk between Hippo and Wnt pathways. YAP preferentially acts as a transcriptional co-regulator of Hippo signaling pathway or as a regulator in the Wnt signaling pathway depending on the cell type [32]. The inhibition of YAP by RA-V, as demonstrated by Ji et al, could be responsible for the Wnt inhibition observed from our study.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…A recent review on YAP describes its crosstalk between Hippo and Wnt pathways. YAP preferentially acts as a transcriptional co-regulator of Hippo signaling pathway or as a regulator in the Wnt signaling pathway depending on the cell type [32]. The inhibition of YAP by RA-V, as demonstrated by Ji et al, could be responsible for the Wnt inhibition observed from our study.…”
Section: Resultssupporting
confidence: 66%
“…The crosstalk between cancer signaling pathways plays several complex roles in cancer and the identifying targets modulating these pathways serve as the current focus on the cancer treatment approach. Among them, the Wnt signaling pathway is known for its involvement in cancer initiation and progression via the activation of β-catenin signaling [32]. It has been reported that the cytoplasmic YAP is involved in regulating the tissue differentiation and migration of tumor cells by binding to β-catenin [36].…”
Section: Discussionmentioning
confidence: 99%
“…The E-cadherin-mediated AJ structure in the cell membrane sequestrates β-catenin, a key component of Wnt signaling, inhibiting Wnt signaling [ 37 ]. In addition, β-catenin binds to YAP and regulates its activity by sequestrating YAP in the cytoplasm [ 16 ], inhibiting malignant transformation. Therefore, reduction of Wnt signaling and YAP activity in EC96 cells is unsurprising.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of β-catenin in densely cultured MCF10A cells decreases phosphorylation of the S127 residue of YAP and its nuclear accumulation [ 15 ]. β-catenin, a major effector of the Wnt signaling pathway and a component of AJs, binds with YAP directly and mediates cross-regulation between the Hippo and Wnt signaling pathways, regulating cell phenotypes including proliferation [ 16 ]. Several components of TJs regulate Hippo and YAP activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The APc/axin/GSK3β complex from the Wnt/β-catenin pathway and SMAd7 can alter the function of SMAd proteins of the TGF-β pathway, resulting in delayed apoptosis and metastasis, and an increased cell growth and division. Studies have indicated that the dsh protein of the Wnt pathway influences the translocation of YAP protein (Hippo pathway) by close contact inhibition of E-cadherin (238,239).…”
Section: Crosstalk Among Various Pathwaysmentioning
confidence: 99%